The development of a consensus statement for the prescription of powered wheelchair standing devices in Duchenne muscular dystrophy. Issue 10 (8th May 2022) - Schofield, C.; Evans, K.; Young, H.; Paguinto, S-G.; Carroll, K.; Townsend, E.; Kiefer, M.; McGuire, M.; Sodhi, J.; Bray, P.; Bayley, K.; Vorster, N. M.; et al.
Abstract: Purpose: To develop a consensus statement for the prescription of a Powered Wheelchair Standing Device (PWSD) in young people with Duchenne muscular dystrophy (DMD). Materials and methods: An international multidisciplinary panel comprising clinicians and users (young people with DMD) along with their parents was consulted. A literature review was undertaken and a Delphi method was utilised to generate consensus statements. To supplement limited literature, round one of the Delphi process comprised questions consistent with the International Classification of Functioning, Disability and Health model of disability to generate items based on expert opinion and was completed by 38 clinicians and nine users. Thirty-seven participants completed two further rounds rating the importance of each item with a five-point scale. Agreement of 70% or more participants for items indicated consensus. Results: Consensus was reached for 47 of 80 items. Tolerance and comfort in supported standing for at least 10 min, ankle contracture less than 10 degrees and user goals reflecting motivation to use the standing function were agreed as necessary in guiding the decision to trial a PWSD. Evidence of family, therapist and servicing support were also considered critical in enabling continuity of PWSD use. Conclusions: PWSD is a mobility option that offers choice, control and opportunity for independence. This consensus statement can assist clinicians with decision-making around factors influencing successful implementation and optimisation of PWSD for young people with DMD. Implications for Rehabilitation: Tolerance and comfort in supported standing for at least 10 minutes, ankle contracture limited to less than 10 degrees and the child's goals reflecting motivation to use the standing position were agreed to be necessary considerations in guiding the decision to trial a PWSD. Trialling a PWSD when the child is predicted to lose the ability to walk within a one to two year period was recommended although a PWSD could be suitable for a child who was unable to walk. Evidence of family, therapist and servicing support was considered critical in enabling continuity of PWSD use.